Among military personnel Evaluation of systemic hemodynamic parameters during unilateral spinal anesthesia combined with epidural analgesia - Rakhmankulov E.J. Ph.D; Associate Professor Mirrakhimova S.Sh Ph.D; Professor Avakov V.E; Chakganov O'.A (Genius Journals, 2025)
Evidence for the superior quality of spinal anesthesia compared with epidural anesthesia is provided by studies that show a significantly lower increase in blood cortisol levels during abdominal surgery with spinal anesthesia [31, 66; pp. 42-64] and that epidural analgesia provides sufficient blockade of the hormonal response to operative stress only when supplemented with spinal anesthesia [66; pp. 42-64]. There are objective conditions for the occurrence of such problems, which are determined by the anatomical features of the epidural space. In the case of repeated epidural blocks in one patient, adhesions in the epidural space formed after the first procedure may serve as a factor impeding the spread of anesthetic, which indicates a higher incidence of anesthetic failure in patients with a “history of epidural anesthesia”. [14; p. 19-23, 32; 33-42, 80; 299-301- b].
Keywords: sensory; epidural analgesia; unilateral spinal anesthesia